Evolution and Epidemiology of Multidrug-Resistant $\textit{Klebsiella pneumoniae}$ in the United Kingdom and Ireland - Moradigaravand, D; Martin, V; Peacock, SJ; Parkhill, J (American Society for Microbiology, 2017)
$\textit{Klebsiella pneumoniae}$ is a human commensal and opportunistic pathogen that has become a leading causative agent of hospital-based infections over the past few decades. The emergence and global expansion of hypervirulent and multidrug-resistant (MDR) clones of $\textit{K. pneumoniae}$ have been increasingly reported in community-acquired and nosocomial infections. Despite this, the population genomics and epidemiology of MDR $\textit{K. pneumoniae}$ at the national level are still poorly understood. To obtain insights into these, we analyzed a systematic large-scale collection of invasive MDR $\textit{K. pneumoniae}$ isolates from hospitals across the United Kingdom and Ireland. Using whole-genome phylogenetic analysis, we placed these in the context of previously sequenced $\textit{K. pneumoniae}$ populations from geographically diverse countries and identified their virulence and drug resistance determinants. Our results demonstrate that United Kingdom and Ireland MDR isolates are a highly diverse population drawn from across the global phylogenetic tree of $\textit{K. pneumoniae}$ and represent multiple recent international introductions that are mainly from Europe but in some cases from more distant countries. In addition, we identified novel genetic determinants underlying resistance to beta-lactams, gentamicin, ciprofloxacin, and tetracyclines, indicating that both increased virulence and resistance have emerged independently multiple times throughout the population. Our data show that MDR $\textit{K. pneumoniae}$ isolates in the United Kingdom and Ireland have multiple distinct origins and appear to be part of a globally circulating $\textit{K. pneumoniae}$ population. IMPORTANCE $\textit{Klebsiella pneumoniae}$ is a major human pathogen that has been implicated in infections in healthcare settings over the past few decades. Antimicrobial treatment of $\textit{K. pneumoniae}$ infections has become increasingly difficult as a consequence of the emergence and spread of strains that are resistant to multiple antimicrobials. To better understand the spread of resistant $\textit{K. pneumoniae}$, we studied the genomes of a large-scale population of extensively antimicrobial-resistant $\textit{K. pneumoniae}$ in the United Kingdom and Ireland by utilizing the fine resolution that whole-genome sequencing of pathogen genomes provides. Our results indicate that the $\textit{K. pneumoniae}$ population is highly diverse and that, in some cases, resistant strains appear to have spread across the country over a few years. In addition, we found evidence that some strains have acquired antimicrobial resistance genes independently, presumably in response to antimicrobial treatment.
Keywords: Drug Resistance, Multiple, Bacterial; Genetic Variation; Hospitals; Humans; Ireland; Klebsiella Infections; Klebsiella pneumoniae; Molecular Epidemiology; Molecular Typing; Phylogeny; United Kingdom